FAMILY ANTHOMYIIDAE - Grisales, Diana; Lopes, André César; de Carvalho, Claudio J. B. (Zootaxa, 2016)
Here we catalogue six species in four genera of Anthomyiidae (Anthomyia, Calythea, Delia, and Emmesomyia) from Colombia and provide geographical information for all species, when available.